1972
DOI: 10.1071/bi9720379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Composition of Diluent, Method of Addition of Glycerol, Freezing Rate, and Storage Temperature on the Revival of Ram Spermatozoa After Deep-Freezing

Abstract: The addition of 6% (vJv) egg yolk to a synthetic diluent [247 mM glucose, 49 mM NaCI, 5 mM KCI, 5 mM phosphate buffer, and 7·5% (vJv) glycerol] improved the survival of ram spermatozoa after deep·freezing. Judging by the activity of spermatozoa after thawing, a single addition of glycerol to the diluted semen at 5°C was as effective as multiple additions giving a graded increase of glycerol concentration over a period of 20 min. Reciprocal replacement of the sodium chloride of the diluent by an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1975
1975
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…No advantage was gained by this modification in freezing (expts 1 and 2) and it may therefore be concluded that a temperature fluctuation coinciding with the formation of ice crystals was not detrimental to the spermatozoa. Entwistle and Martin (1972) found that less than 6% egg yolk in the diluent used for freezing ram spermatozoa in ampoules resulted in reduced survival. In experiment 2, however, no difference was observed between the survivals of spermatozoa in diluents with egg yolk levels ranging from 3 to 12 %, and the degree of acrosome disruption was similar in all diluents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…No advantage was gained by this modification in freezing (expts 1 and 2) and it may therefore be concluded that a temperature fluctuation coinciding with the formation of ice crystals was not detrimental to the spermatozoa. Entwistle and Martin (1972) found that less than 6% egg yolk in the diluent used for freezing ram spermatozoa in ampoules resulted in reduced survival. In experiment 2, however, no difference was observed between the survivals of spermatozoa in diluents with egg yolk levels ranging from 3 to 12 %, and the degree of acrosome disruption was similar in all diluents.…”
Section: Discussionmentioning
confidence: 99%
“…However, uncontrolled variations in the freezing rate and pattern of crystallization occur within the sample because of its volume and dimensions, and this has hindered more critical studies of the freezing conditions. In addition, the freezing curve recorded by a thermocouple within the sample has a characteristic deviation from linearity (Entwistle and Martin 1972).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Οι βλάβες αυτές αφορούσαν κυρίως το ακρόσωμα και την κυτταρική μεμβράνη. Όμως, οι Watson και Martin (1972) συγκρίνοντας τις βλάβες που προκαλούνται εξαιτίας της κατάψυξης στο ακρόσωμα σπερματοζωαρίων ταύρου και κριού διαπίστωσαν ότι η μικρή υπεροχή των καταψυγμένων σπερματοζωαρίων του ταύρου, ως προς την ακεραιότητα του ακροσώματος, δε δικαιολογεί από μόνη της τη μεγάλη διαφορά στη γονιμότητα του καταψυγμένου σπέρματος μεταξύ των δύο ειδών. Η τεχνική της σπερματέγχυσης και ιδιαίτερα το σημείο της τοποθέτησης του καταψυγμένου σπέρματος διαπιστώθηκε ότι επηρεάζουν σοβαρά το ποσοστό συλλήψεων.…”
Section: δυσμενής επίδραση της κατάψυξης και απόψυξης στα σπερματοζωάριαunclassified